Development and validation of new RP-HPLC method for the determination of gliclazide in tablet dosage form - Alaama, Mohamed; Helal Uddin, A.B.M.; Abbas, Syed Atif (College of Pharmacists of Buenos Aires Province, Argentina, 2017)
A new sensitive and economic analytical method for the analysis of gliclazide in tablet dosage form was developed and validated using commercial HPLC instrument with modern ultra-performance liquid chromatography column. Samples were analysed using Agilent 1100 Series RP-HPLC equipped with a binary pump and auto injector. Samples were injected into Xselect HSS C18 XP column (2.1 × 100 mm, 2.5 μm), 2.5 μm) and the mobile phase consisted of triethylamine buffer 0.3% (pH = 3 adjusted using phosphoric acid) and acetonitrile in the ratio of 50:50 v/v. The flow rate was 0.4 mL/min and the DAD de- tector was used for the detection and the wavelength was 229 nm. The method was validated according to ICH guidelines. The retention time for gliclazide peak was 3.437 ± 0.41 min with the total run time of 6 min with total solvent consumption of 2.4 mL per run. The method was found linear over the range 0.1-10 μg/mL with coefficient of determination R2 of 0.9997. The recovery was 98.09-100.19 %, and the method showed high precision and repeatability. Degradation pathway of gliclazide was studied following differ- ent types of stress degradation which are base, acid, UV, and oxidization. All validated parameters were in the acceptable range of ICH requirements. In conclusion, a new, rapid, sensitive, and economic method was developed and validated for the analysis of gliclazide in tablet dosage form. RESUMEN. Se desarrolló un nuevo método analítico sensible y económico para el análisis de gliclazida en forma de dosificación de comprimidos y se validó usando HPLC con una columna moderna de cromatografía líquida de ultra rendimiento. Las muestras se analizaron utilizando un equipo RP-HPLC Agilent Serie 1200 equipado con bomba cuaternaria y autoinyector. Las muestras se inyectaron a una columna de agua C18 HSS (2,1 × 100 mm, 2,5 μm) y la fase móvil consistió en tampón de trietilamina 0,3% (pH = 3 ajustado usando ácido fosfórico) y ace- tonitrilo en la relación 50:50 v/ v. El caudal era de 0,4 mL/ min y se utilizó un detector UV y la longitud de onda fue de 229 nm. El método fue validado de acuerdo con las pautas de ICH. El tiempo de retención para el pico de gliclazida fue de 3,437 ± 0,41 min con el tiempo total de ejecución de 6 min y un consumo total de disolventes de 2,4 mL por ciclo. El método se encontró lineal en el intervalo de 0,1-10 μg/mL con un coeficiente de determi- nación R2 de 0,9997. La recuperación fue de 98,09-100,19%, y el método mostró alta precisión y repetibilidad. La vía de degradación de gliclazida se estudió después de diferentes tipos de degradación del estrés que son base, ácido, UV y oxidación. Todos los parámetros validados estaban dentro del rango aceptable de los requisitos de ICH. En conclusión, se desarrolló y validó un nuevo método rápido y sensible para el análisis de gliclazida en forma de tableta.